The Use Of Picture Media To Enhance Students’ Skills In Writing Procedure Text - Wahyuda; Nuzulul Isna (Journal Informatic, Education and Management (JIEM), 2025)
This study investigates the effectiveness of picture media in enhancing students’ procedural text writing skills through a quasi-experimental design involving 60 senior high school students, equally divided into an experimental group and a control group. The experimental group received instruction supported by picture media, whereas the control group was taught using conventional methods. Pretests and posttests were administered, with data analyzed using the Wilcoxon Signed-Rank Test for the experimental group (non-normal distribution), the Paired Sample t-Test for the control group, and the Mann–Whitney U Test to compare posttest scores between groups. The findings reveal that both groups demonstrated significant improvement; however, the experimental group achieved a greater mean gain score (27.26) compared to the control group (15.50) and a higher posttest mean (83.43 vs. 65.50). The Mann–Whitney U Test produced a p-value of 0.000, confirming a statistically significant difference in performance. The greatest improvement was observed in content development, followed by organization and vocabulary. These results highlight the effectiveness of picture media in fostering students’ comprehension, engagement, and ability to sequence ideas coherently when writing procedural texts. The study concludes that picture-based instruction offers a more impactful and inclusive pedagogical approach for teaching procedural text writing in senior high schools.